2013
DOI: 10.1111/jhn.12078
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss expectations and body dissatisfaction in young women attempting to lose weight

Abstract: We observed a mismatch between clinical and personal expectations, and social pressure and interpersonal relationships appear to have a prominent role with respect to influencing the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
(35 reference statements)
2
18
1
5
Order By: Relevance
“…Many of the findings were as expected; for example, our findings were consistent with previous studies in young women, with larger weight-loss expectations reported in line with higher BMI (35,56) . However, other findings were novel.…”
Section: Differences By Age Bmi and Socio-economic Statussupporting
confidence: 82%
See 2 more Smart Citations
“…Many of the findings were as expected; for example, our findings were consistent with previous studies in young women, with larger weight-loss expectations reported in line with higher BMI (35,56) . However, other findings were novel.…”
Section: Differences By Age Bmi and Socio-economic Statussupporting
confidence: 82%
“…Women (mean age of 38·2 years) who enrolled in a weight management intervention were more likely to report appearance rather than improving health as the key motivation for enrolment, when compared with males (17) . Findings from the US National Weight Control Registry suggest that young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years) who maintained a weight loss for at least 1 year were more likely to report improved appearance or social factors as their primary motivators for weight loss and less likely to report health concerns as their motivation, when compared with older adults (36-50 years) (39) . These findings suggest that young women have different motivations for wanting to control their weight; however, these studies were restricted to individuals already enrolled in a weight-loss intervention or who had achieved successful weight-loss maintenance and therefore may not be representative of young women generally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with self‐regulation theory , in which individuals with ambitious goals exhibit increased motivation and persistence, resulting in more effortful goal striving and progress. To reconcile this mixed picture of evidence, it has been suggested that the relationship between weight loss and WLEs is mediated by other variables ; these may include age , the perceived origin of the WLEs , body dissatisfaction and disordered eating .…”
Section: Introductionmentioning
confidence: 99%
“…Most previous research on body dissatisfaction and weight loss has focused on individuals with normal weight or on adolescents, but not on adults with obesity. However, there is evidence that improving body image or body appearance (rather than health) may be an influential factor for weight loss desire [19,20], since higher weight loss goals result from greater body image concerns among obese individuals in general, and among women with obesity in particular [21]. The perceived need of losing weight and the wish to achieve greater body weight reductions might be linked to anxiety about body image concerns [20,23], resulting in disordered health behavior [22].…”
Section: Introductionmentioning
confidence: 99%